Anatomical responses of roots and yield of cocoa (Theobroma cacao L.) to K fertilization doses - Shodiq, Muhammad Syaiful; Susila Putra, Eka Tarwaca; Rofiqo Irwan, Siti Nurul (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Cocoa is one of important commodities for the economy of Indonesia. However, national exports of the commodity has declined due to decreasing of domestic cocoa production. For enhancing cocoa production, potassium fertilization is required. Potassium (K) is an essential macronutrient in the physiology, anatomy, and yields processes. Anatomically, K is needed in the elongation of meristem tissue as well as for increasing the yields of fruit and seed. The objectives of this research included the study of the effect of K fertilizer dose and determination of optimum K doses on root anatomy development as well as the yield of cocoa pods. This research was conducted on the cocoa plantation of PT. Pagilaran. Applied doses of K fertilization consisted of 0, 150, 300, 450, and 600 g KCl/plant in Randomized Complete Block Design (RCBD) with 5 replications. Observed variables consisted of root anatomy and yield of cocoa pods. The results indicated that the dose of K fertilization significantly influenced both stele and xylem diameters of cocoa roots but insignificantly effected the thickness of cork tissue, phloem diameter, and the thickness of cambium tissue. Moreover, the dose also showed significant effect on the number of beans per pod, the weight of 100 beans, as well as the fresh and dry weight of beans per plant. It was also revealed that the dose showed no significant effect on length, diameter, and weight of the cocoa pods. It implied that K fertilization dose had effect on root anatomical properties and yield of cacao.